Compare nasal endoscopy with Computed Tomography scans for chronic rhinosinusitis detection in adult Iraqi patients - Ali lafta Salman (Diyala Journal of Medicine)
Background: Chronic rhinosinusitis (CRS) is often diagnosed based on clinical features. Assurance in this context is based on the finding of inflammatory features during nasal endoscopy and computed tomography (CT) scans of the paranasal sinuses. While a CT scan is considered the most reliable method, research has shown that nasal endoscopy is also valuable and can sometimes provide additional information to supplement the CT scan in diagnosing CRS.